FERMENTASI MOLASE DARI TETES TEBU SEBAGAI ALTERNATIF BAHAN BAKAR TERBARUKAN - Adean Mayasri (Lantanida Journal, 2023)
Molasses fermentation from molasses has been studied as an alternative to renewable energy. The goal of this research was to determine molasses fermentation as an alternative to renewable energy. The goal of this research was to monitor the alcohol concentration and pH levels during the fermentation process. This study employed a completely randomized design (CRD) method with two components. Factor A is the amount of time required for aeration. Molasses dilution is factor B. Factor A was tested across four different time periods: 24, 48, 72, and 96 hours. Factor B was tested using three different ratios: 1: 1.5, 1: 2, and 1: 2.5. The calculations of alcohol content FcalcP = 74.35> Ftable (11; 36; 0.05) = 2.07 and Ftable (11; 36; 0.01) = 2.79 revealed that components A and B had a significant impact on the final alcohol content. The BNJ 1% was calculated to be 0.63. This demonstrates that A4B3 is the most effective treatment. FcalcP = 2.85> Ftable (11; 36; 0.05) = 2.07 and Ftable (11; 36; 0.01) = 2.79, indicating that factors A and B have a highly substantial effect on acidity (pH). The BNJ 5% was obtained at a value of 0.61. This also demonstrates the optimal acidity conditions in A4B3 therapy. Based on these findings, it is clear that aeration for 96 hours and dilution with a 1: 2.5 ratio produce the greatest outcomes and the maximum alcohol content. At a pH of 4.45, the average bioethanol content is 6.31%.